Zastosowanie metody zdyskontowanych przepływów pieniężnych w wycenie spółek technologicznych - Jerzemowska, Magdalena; Hryniewicz, Grzegorz (Selected Problems Concerning the Valuation of Technology Companies, 2005)
The aim of the paper was to assess DCF method with respect to valuation of High Tech companies. After examinations we formulated a conclusion that these companies require application of valuation method depended on generated cash-flow. Pres and con concerning the application of that method are included in the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 176-183